La transition en tension : comment les supermarchés coopératifs et participatifs mettent-ils en œuvre le changement social ? - Ali Romdhani; Guglielmo Fernandez Garcia; René Audet (VertigO)
Over the past decade, we have observed in France a strong enthusiasm for the food coop model, which offers citizens the opportunity to reclaim food distribution in order to offer quality products at a fair price. Based on the case study of Breizhicoop in the city of Rennes (France), we demonstrate how a narrative of social change is articulated around two structuring tensions: product offering and store management. From these results we discuss two limits addressed to food coops, namely the reproduction of the classic entrepreneurial organisation and the formation of a homogeneous and exclusive community. We address several learnings for the socio-ecological transition.